2010
DOI: 10.1007/s00405-010-1220-4
|View full text |Cite
|
Sign up to set email alerts
|

Shepard grommet tympanostomy tube complications in children with chronic otitis media with effusion

Abstract: The objective of this study was to determine tympanostomy tube complications in children with chronic otitis media with effusion who were treated with Shepard grommet tympanostomy tube insertion. This tube type was selected as it is the most commonly used one in our clinic. The medical records of 162 ears of 87 children (52 male and 35 female) were reviewed retrospectively. The children were between 3 to 16 years old (mean age = 8.1 +/- 3.1). The patients were followed up 6-66 months (mean 23.3 +/- 14.9 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 19 publications
0
15
1
1
Order By: Relevance
“…12,23 The clinical observations indicate that the frequency of myringosclerosis is much higher in tympanic membranes with tympanostomy tube insertion than in tympanic membranes with no tympanostomy tube insertion (23-70% and 0-13%, respectively). 5,11,[23][24][25][26][27][28][29][30] It was also observed that the myringosclerosis rate increased with a larger size of tube, several tube insertions and time of tympanostomy tube stay. 25,29,31,32 Based on computer modeling, it has been shown that ventilation tube insertion induces shear stress in the structure of the tympanic membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,23 The clinical observations indicate that the frequency of myringosclerosis is much higher in tympanic membranes with tympanostomy tube insertion than in tympanic membranes with no tympanostomy tube insertion (23-70% and 0-13%, respectively). 5,11,[23][24][25][26][27][28][29][30] It was also observed that the myringosclerosis rate increased with a larger size of tube, several tube insertions and time of tympanostomy tube stay. 25,29,31,32 Based on computer modeling, it has been shown that ventilation tube insertion induces shear stress in the structure of the tympanic membrane.…”
Section: Discussionmentioning
confidence: 99%
“…25,29,34 Typically, tympanosclerotic changes proceed via the destruction of connective tissue followed by fibrosis resulting in elevated deposition of collagens and subsequent calcification of tissues in the middle ear. A recent histological study demonstrated that a healthy human tympanic membrane consists of collagen type I, II, III and IV.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cases in which tympanostomy tubes, sludge, and ear mould impression material become middle-ear foreign bodies have repeatedly been reported [3][4][5][6][7]. In addition, the prevalence of chronic tympanic membrane perforations is high [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that up to 17% of patients who have tympanostomy tubes placed will develop some sort of complications [2,3]. These include otorrhea, peritubal drum atrophy, scarring, granulation tissue, tympanosclerosis, persistant perforation, blockage of the tube lumen, premature extrusion, cholesteatoma formation and tympanostomy tube displacement into the middle ear [4][5][6].…”
Section: Introductionmentioning
confidence: 99%